Efektivitas Rebusan Air Sirih Hijau terhadap Penyembuhan Luka Perineum pada Ibu Post Partum - Nona Sari; Fajar Sari Tanberika; Rifa Yanti; Rika Ruspita (LPPM Universitas Bhamada Slawi PSDKU D III Kebidanan Kampus Kota Pekalongan, 2026)
Perineal wounds are a common complication among postpartum mothers caused by spontaneous laceration or episiotomy, which, if not properly managed, may lead to bleeding or infection. Green betel leaf (Piper betle) decoction is a promising non-pharmacological alternative owing to its antiseptic properties and its potential to accelerate wound healing. This study aimed to determine the effectiveness of green betel leaf decoction on perineal wound healing among postpartum mothers at Rimba Melintang Community Health Center, Rokan Hilir Regency. This quantitative study used a quasi-experimental two-group pretest-posttest design, conducted from June to July 2025 among 32 respondents divided into 16 intervention and 16 control participants selected through purposive sampling. Data were collected using the REEDA scoring observation sheet and analyzed univariately and bivariately using the Wilcoxon and Mann-Whitney tests. Results showed a significant decrease in wound scores in the intervention group (p=0.000) and a significant difference between groups on the Mann-Whitney test (p=0.001). Green betel leaf decoction was effective in accelerating perineal wound healing and may be considered a safe complementary therapy for postpartum mothers.